Seismic collapse performance of steel special moment frames designed using different analysis methods. Issue 2 (May 2021) - Kim, Taeo; Han, Sang Whan
Building structures designed according to current seismic design codes should satisfy the seismic performance objectives specified in codes during big earthquake events. ASCE 7-16 specifies that risk category I and II structures should have a probability of collapse less than 10% against the maximum considered earthquake (MCE) shaking hazard. ASCE 7-16 provides four analysis methods to calculate the seismic demands on structures. In this study, 4-, 8-, 12-, and 16-story steel special moment frames (SMFs) are designed using the two most popular elastic analysis methods: the equivalent lateral force (ELF) method and the modal response spectrum analysis (RSA) method. The collapse probabilities of these structures are estimated against MCE shaking hazards according to FEMA P695. It is observed that the collapse probabilities of these structures vary according to analysis methods used for design. To improve the seismic collapse performance of SMFs, a modified method is proposed.